1996
DOI: 10.1007/s004410050583
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and migration-related zonation of K + -ATPase activities in the oxyntic cell lineage of adult cattle

Abstract: Activities of the H+, K(+)-ATPase and the Na+, K+, ATPase have been localized in the morphologically heterogeneous oxyntic cell lineage of adult bovine abomasal mucosa, by means of K(+)-dependent paranitrophenylphosphatase (K(+)-pNPPase) histochemistry. At the light- and electron-microscopic level, only members of the mature oxyntic cell population within the oxyntic glandular base exhibit strong enzyme activity. Superficial oxyntic cells of the proximal isthmus and deep pit, arising from the upward migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In addition to stem cells, the precursors of pit and neck cells, the isthmus of the stomach contains parietal cells with different degrees of maturation [13]. Functional and morphological heterogeneity of parietal cells has been reported [30–32]. Although we were unable to determine precisely whether Msi‐1 is expressed in mature or immature parietal cells, the size, shape and significant H + /K + ‐ATPase staining of the Msi‐1 cells suggest that they are differentiated.…”
Section: Discussionmentioning
confidence: 79%
“…In addition to stem cells, the precursors of pit and neck cells, the isthmus of the stomach contains parietal cells with different degrees of maturation [13]. Functional and morphological heterogeneity of parietal cells has been reported [30–32]. Although we were unable to determine precisely whether Msi‐1 is expressed in mature or immature parietal cells, the size, shape and significant H + /K + ‐ATPase staining of the Msi‐1 cells suggest that they are differentiated.…”
Section: Discussionmentioning
confidence: 79%
“…To date, studies of the functional heterogeneity of gastric parietal cells have been reported along the gland axis Firth 1983, 1988;Kressin 1996;Karam et al 1997). By means of enzyme histochemistry for K + -NPPase, Firth (1983, 1988) demonstrated a high activity of H + /K + -ATPase in parietal cells locating at the luminal segment (consisting of the pit and the upper neck region) of mouse gastric glands.…”
Section: Discussionmentioning
confidence: 97%
“…It is generally accepted that the parietal cells are produced in the isthmus and migrate either upward to the pit region (referred to as pit-parietal cell hereafter) or downward to the glandular base via the neck region (referred to as glandular-parietal cells) (Karam 1993(Karam , 1999. Studies of the heterogeneity of gastric parietal cells have been reported along the gland axis by means of histochemical techniques (Coulton and Firth 1983;Suganuma et al 1984;Coulton and Firth 1988;Kressin 1996;Karam et al 1997). However, little is known about the physiological signiWcance of the heterogeneity between the pit-and the glandular-parietal cells mainly because of a lack of reliable experimental model.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that parietal cells function differently throughout their lifespan (12,13). Parietal stem cells reside in the neck of the gastric pit.…”
Section: Discussionmentioning
confidence: 99%
“…As parietal cells mature, they migrate downward toward the base of the pit. It has been suggested that mouse parietal cells secrete acid in the early phase of their lives on the basis of electron microscopy and [ 3 H]thymidine radioautographic analyses (12,13). As they mature toward the base of the pit, parietal cells secrete less acid and more water.…”
Section: Discussionmentioning
confidence: 99%